"PENGELOLAAN MODAL KERJA USAHA MIKRO KECIL “KETAN SUSU YUK!” " - Selfiana Selfiana; Rafie Agung Nugroho (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
The purpose of this study was to determine the working capital turnover, cash turnover cycle and sales of "Ketan Susu Yuk." The research was conducted using descriptive qualitative methods and using interview methods to obtain data regarding working capital requirements used by business operations, namely the cash turnover cycle, projected cash needs, sales and activity ratios. The “Ketan Susu Yuk” business sells a menu of processed sticky rice, processed baked bananas and processed fried tempeh. Other supporting menus are various toppings that will be served according to the customer's taste and hot brewed tea drinks. The results showed that the most effective use of cash was in processed baked bananas, namely 3 times with a profit margin of 63%. The owner must innovate in increasing sales of the sticky rice menu.